Composite fiber material with high tensile strength and self-repairing function for safety rope and preparation process thereof

CN122980068APending Publication Date: 2026-10-27SHANDONG BINZHOU ANHUI ROPE NET CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611113535.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

现有自修复安全绳相关技术仍存在明显短板,主要体现在以下方面:1)自修复交联体系单一,仅能在高温、干燥或高湿单一环境下起效,户外复杂工况适配性差,多次修复后力学衰减明显;2)多采用表面涂覆实现自愈,涂层磨损后修复功能失效,无法修复纤维内部深层裂纹;内嵌微胶囊方案缺少界面增韧设计,会大幅降低纤维抗拉强度,达不到载人安全绳标准;3)无法监测内部隐性疲劳裂纹,安全隐患难提前排查;高强纤维表面惰性大,与基体界面易分层,且现有制备工序分散,产品稳定性差

Benefits of technology

(1)采用UHMWPE/对位芳纶复配承载芯层采用等离子+多巴胺双界面增强体系,搭配中间层芳纶纳米纤维桥接双重增韧,大幅提升芯层与功能层界面粘结强度,受力无分层开裂,长期循环拉伸下力学衰减缓慢。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1784712063633-000001
    Figure REF-OBJ-1784712063633-000001
  • Figure REF-OBJ-1784712063633-000002
    Figure REF-OBJ-1784712063633-000002
Patent Text Reader

Abstract

The present application relates to the technical field of functional composite fibers, and particularly relates to a composite fiber material with high tensile and self-repairing functions for safety ropes and a preparation process thereof, which realizes multi-working-condition self-repairing, synchronously realizes internal micro-crack resistance early warning, and has high tensile mechanical properties, long-acting self-repairing properties and outdoor use safety by means of a three-layer coaxial gradient integrated composite structure, a triple dynamic reversible key synergistic crosslinking intermediate functional layer, dopamine interface modification and a low-dosage conductive sensing filler, and a matching continuous integrated preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional composite fiber technology, and in particular to a composite fiber material for safety ropes with high tensile strength and self-healing function, and its preparation process. Background Technology

[0002] With the continuous upgrading of safety standards in high-altitude operations, fire rescue, and outdoor climbing, high-strength flexible safety ropes have become core equipment for personnel protection. Currently, the industry generally uses high-strength fibers such as UHMWPE and para-aramid to manufacture safety ropes. These materials have advantages such as high tensile strength, impact resistance, and wear resistance, which can meet the basic mechanical requirements of high-altitude load-bearing protection. They are gradually replacing traditional nylon and polyester ropes and becoming the mainstream material for high-end safety ropes.

[0003] However, these fibers lack self-repair capabilities. Long-term friction, alternating wet and dry conditions, and UV aging can easily lead to internal microcracks, which can accumulate and cause rope breakage. Existing self-healing safety rope technologies still have significant shortcomings, mainly in the following aspects: 1) The self-healing cross-linking system is singular, only effective in high-temperature, dry, or high-humidity environments, resulting in poor adaptability to complex outdoor conditions and significant mechanical attenuation after multiple repairs; 2) Self-healing is often achieved through surface coating, but the repair function fails after coating wear, and it cannot repair deep internal fiber cracks; the embedded microcapsule solution lacks interface toughening design, significantly reducing fiber tensile strength and failing to meet the standards for manned safety ropes; 3) Internal latent fatigue cracks cannot be monitored, making it difficult to detect safety hazards in advance; high-strength fibers have high surface inertness, easily delaminating at the matrix interface, and existing preparation processes are fragmented, resulting in poor product stability.

[0004] Therefore, it is of great value to develop a composite fiber material for safety ropes that combines high tensile strength, long-term self-healing under multiple working conditions, damage warning, and strong interfacial bonding. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a composite fiber material for safety ropes with high tensile strength and self-healing capabilities, along with its preparation process. Through a three-layer coaxial gradient integrated composite structure, a triple dynamic reversible bond synergistic cross-linked intermediate functional layer, dopamine interface modification, and low-dosage conductive sensing filler, it achieves autonomous repair under multiple working conditions and simultaneously provides early warning of internal micro-crack resistance. Coupled with a continuous integrated preparation process, it balances the high tensile mechanical properties, long-term self-healing performance, and outdoor safety of the safety rope.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides a composite fiber material for safety ropes with high tensile strength and self-healing function. The composite fiber material has a three-layer coaxial gradient composite fiber structure, consisting of a load-bearing core layer, an intermediate functional layer, and a protective skin layer from the inside out. The load-bearing core layer comprises 65%–70% of the radial thickness, the intermediate functional layer 20%–25%, and the protective skin layer 5%–10%. The load-bearing core layer is composed of UHMWPE filament and para-aramid filament; The intermediate functional layer, by weight, comprises the following raw materials: 100 parts polyether-type polyurethane elastomer, 2.0-3.0 parts aromatic disulfide chain extender, 1.5-2.5 parts acylhydrazone prepolymer, 1.0-2.0 parts tannin-based polyhydroxy modifier, 1.0-1.5 parts aramid nanofibers, 0.8-1.2 parts conductive filler, and 0.2-0.4 parts hydrolysis stabilizer; The protective skin layer comprises, by weight, 100 parts weather-resistant polyurethane, 4.0 to 8.0 parts nano alumina, 1.5 to 2.5 parts ultraviolet absorber, and 3.0 to 5.0 parts tannin-based polyhydroxy modifier.

[0007] This invention first uses the load-bearing core layer as the main load-bearing component of the composite fiber, meeting the national standard mechanical indicators for breaking tensile strength and fall impact of high-altitude passenger safety ropes. Secondly, the intermediate functional layer constructs a triple dynamic reversible cross-linked network of aromatic disulfide bonds, acylhydrazone bonds, and tannin hydroxyl hydrogen bonds, combined with conductive fillers to achieve damage warning, while dispersing aramid nanofibers to achieve interface toughening. Finally, the protective skin layer constructs a thin-layer weather-resistant protective structure to isolate sand and gravel friction, ultraviolet light, and rainwater erosion, delaying the aging of internal dynamic bonds and polymer matrix, while also possessing basic hydrogen bond self-healing capabilities.

[0008] In some embodiments, the aromatic disulfide chain extender is 4,4'-diaminodiphenyl sulfide.

[0009] In some embodiments, the acylhydrazone prepolymer is a prepolymerized acylhydrazone monomer obtained by condensation of adipamide and terephthalaldehyde, both of which are commercially available chemical raw materials, obtained through a condensation reaction.

[0010] In some embodiments, the tannin-based polyhydroxy modifier is obtained by ring-opening grafting of tannic acid and trimethylolpropane triglycidyl ether, both of which are commercially available.

[0011] This invention introduces a specific acylhydrazone prepolymer, a tannin-based polyhydroxy modifier, and an aromatic disulfide bond chain extender to construct three types of reversible cross-linking structures: moisture-responsive acylhydrazone bonds, room-temperature hydrogen bonds, and thermally responsive disulfide bonds. These three structures work together to achieve self-repair under various operating conditions.

[0012] In some embodiments, the conductive filler is a composite of graphene and short-cut multi-walled carbon nanotubes, with a mass ratio of 1:(2-4), preferably 1:3; a low total doping amount of 0.8-1.2 parts is sufficient to construct a continuous three-dimensional conductive network in the polyurethane matrix; the carbon nanotubes act as one-dimensional conductive bridges to connect the graphene sheets, synergistically improving the stability of the conductive pathway and the crack resistance response sensitivity, while a small amount of carbon-based filler can help improve the wear resistance and UV aging resistance of the matrix.

[0013] In some embodiments, the hydrolysis-resistant stabilizer is carbodiimide.

[0014] In some embodiments, the raw material for the intermediate functional layer further includes 4.0 to 6.0 parts by weight of urea-formaldehyde shell epoxy microcapsules, wherein the particle size of the urea-formaldehyde shell epoxy microcapsules is 1 to 3 μm.

[0015] In some embodiments, the urea-formaldehyde shell epoxy microcapsules can be homemade or commercially available self-healing microcapsule powders, with the shell being urea-formaldehyde resin and the core liquid being bisphenol A epoxy resin combined with a 2-methylimidazole latent catalyst. For example, they can be purchased from Shanghai Yuyu New Materials.

[0016] This invention can optionally add urea-formaldehyde shell epoxy microcapsules to achieve deep crack filling and repair: the microcapsules have a thin-walled shell of urea-formaldehyde resin and are filled with bisphenol A epoxy core liquid mixed with a latent imidazole curing agent; when the fiber is stressed and a deep tensile crack occurs, the stress tears the capsule wall and releases epoxy. The epoxy and curing agent cross-link and cure at room temperature, forming a high-strength adhesive layer at the crack, filling the wide tear damage that cannot be repaired by dynamic bonds; in conjunction with a triple dynamic reversible cross-linking network, it achieves a dual repair effect of self-healing of micro-crack molecules and epoxy filling and repair of deep cracks, greatly improving the long-term service stability of the safety rope.

[0017] In some embodiments, the mass ratio of UHMWPE filament to para-aramid filament in the bearing core layer is 70-80:20-30; the fineness of both fibers is 1.2-1.5D, and the tensile strength of each fiber is ≥3.8GPa.

[0018] This invention utilizes the complementary advantages of two high-strength fibers: UHMWPE fiber is impact-resistant and wear-resistant, while para-aramid is heat-resistant and creep-resistant. The specific ratio of the two fibers enhances the overall tensile strength, creep resistance, and drop impact resistance.

[0019] In some embodiments, the surface of the load-bearing core fiber is modified by in-situ grafting of dopamine hydrochloride after plasma activation, and a polydopamine nano-adhesive layer is formed on the fiber surface.

[0020] In some embodiments, the tannin-based polyhydroxy modifier is obtained by reacting tannic acid and trimethylolpropane triglycidyl ether at a mass ratio of 1:(0.3-0.4) under weak alkaline catalysis at 60-70°C with stirring and solvent removal. This modifier imparts room-temperature self-healing ability to the skin base, preventing rapid rope failure after surface wear.

[0021] In some embodiments, the composite fiber material exhibits a tensile strength ≥3.3 GPa; a self-healing efficiency ≥88% for 0.05 mm fine cracks after 30 minutes at 25°C and 70% RH; and a strength retention rate ≥86% after repeated repairs at the same location five times. A second aspect of the present invention provides a process for preparing the above-mentioned composite fiber material for safety ropes, comprising the following steps: S1. The UHMWPE and para-aramid blended filaments were subjected to air plasma treatment, then immersed in Tris-HCl buffer containing dopamine hydrochloride for in-situ grafting, and washed and dried. S2. Prepare intermediate functional layer masterbatch and protective skin layer masterbatch according to the formula ratio respectively; S3, three-layer coaxial gradient melt spinning, followed by two-stage hot stretching and deep cryogenic tempering to obtain nascent composite fiber material.

[0022] The UHMWPE and para-aramid fibers used in the core layer have strong surface inertness, and direct bonding with the polyurethane matrix can easily lead to interfacial debonding and delamination. This invention employs plasma activation + in-situ dopamine grafting modification: the blended filaments are etched by air plasma to generate hydroxyl and carboxyl active sites on the fiber surface; then, they are immersed in a Tris-HCl buffer solution containing dopamine hydrochloride, where dopamine polymerizes in situ on the fiber surface to generate a hydroxyl-rich polydopamine nano-adhesive layer; simultaneously, aramid nanofibers are dispersed in the intermediate functional layer, forming a nano-bridging network at the interface between the core layer and the intermediate functional layer, which disperses interfacial stress under stress and prevents delamination and cracking of the multilayer composite fibers; under the synergistic effect of dual interface reinforcement, the shear strength of the interface between the core layer and the intermediate functional layer is significantly improved, avoiding fiber breakage caused by delamination under stress.

[0023] In some embodiments, the modification conditions for step S1 are as follows: plasma power 200-400W, treatment for 90-120s; buffer pH=8-9, dopamine hydrochloride concentration 1.8-2.2g / L, reaction at room temperature for 2-3h, and drying.

[0024] In some embodiments, when preparing the intermediate functional layer masterbatch in step S2, the nanofiller is ultrasonically dispersed at 15-25 kHz. When it contains urea-formaldehyde shell epoxy microcapsules, the mixing should be controlled under the conditions of system temperature < 60°C and stirring speed ≤ 150 r / min; the twin-screw granulation temperature is 165-180°C.

[0025] To prevent premature rupture of urea-formaldehyde shell epoxy microcapsules during processing, specific feeding control conditions are set: after the materials are premixed, the system temperature is reduced to below 60℃, the stirring speed is reduced to ≤150r / min, and then the microcapsule powder is slowly added and mixed at low speed; the selected microcapsules are preferably tannin-urea-formaldehyde copolymer capsules prepared from tannin-modified urea, which can withstand short-term heat up to 180℃ and is suitable for twin-screw granulation and three-layer co-extrusion spinning processing temperatures of 165~180℃. The material has a short residence time in the screw, avoiding large-scale damage to the capsule wall.

[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) The UHMWPE / para-aramid composite load-bearing core layer adopts a plasma + dopamine dual interface reinforcement system, combined with the intermediate aramid nanofiber bridging double toughening, which greatly improves the interfacial bonding strength between the core layer and the functional layer. It does not delamination or crack under stress, and the mechanical decay is slow under long-term cyclic tensile stress.

[0027] (2) A triple reversible cross-linking network of hydrogen bonds, aromatic disulfide bonds and acylhydrazone bonds is constructed simultaneously to achieve self-repair under multiple working conditions such as room temperature drying, high humidity rain, and low friction and heat; the synergistic effect of multiple reversible bonds greatly improves the stability of cyclic repair, and the strength retention rate exceeds 85% after 5 repairs; epoxy microcapsules can be selectively embedded to achieve dual repair of surface micro cracks and internal deep tear cracks.

[0028] (3) The low-doped graphene / carbon nanotubes in the intermediate functional layer form a continuous conductive path. The invisible microcracks inside the fiber can be monitored and warned in real time by the change in resistance, which can identify the risk of rope breakage in advance and make up for the defects of traditional safety ropes that are invisible and difficult to investigate.

[0029] (4) The outer weather-resistant polyurethane skin is combined with wear-resistant nano alumina and ultraviolet absorber to isolate sand and gravel friction, ultraviolet rays and rainwater erosion, delay the aging of internal dynamic bonds and polymer matrix, greatly extend the safety rope replacement cycle and reduce the cost of use.

[0030] (5) The three-layer coaxial integrated molding has no delamination defects, and the tensile, impact and creep resistance of the composite fiber meets the standards for high-altitude manned safety ropes. Detailed Implementation

[0031] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0032] The raw materials used in the following embodiments are from the following sources: UHMWPE filament: Shandong Taiguang Chemical Fiber, model TY-1000, screened 1.2~1.5D monofilament, monofilament tensile strength ≥3.9 GPa; Para-aramid filament: Yantai Taihe New Material Taiplon® para-aramid 1414TP-1000, which is a high-strength graded product with secondary heat setting by the manufacturer. The single filament fineness is 1.2~1.5D and the single filament tensile strength is ≥3.8GPa. Polyether-type 90A polyurethane: Wanhua Chemical, WHT-90A polyether spinning grade TPU granules; Weather-resistant polyurethane: Covestro Desmopan DP3685AU, spinning grade; Aramid nanofibers: Aramid nanofiber powder from Taihe New Materials.

[0033] Preparation Example 1 Preparation method of tannic acid modified urea: Take 100 parts by mass of urea and dissolve it in 400 parts of anhydrous ethanol. Add 35 parts of tannic acid and stir to dissolve at room temperature. Then add 2 parts of triethylamine, stir evenly, and heat to 65℃ and stir to react for 4 hours. After the reaction is completed, remove all ethanol by vacuum distillation, cool and pulverize to obtain tannic acid modified urea.

[0034] Preparation Example 2 The preparation method of urea-formaldehyde shell epoxy microcapsules includes the following steps: 1) By weight, 100 parts of E51 epoxy resin and 3 parts of 2-methylimidazole are stirred evenly at room temperature to obtain epoxy core liquid for later use; 1.2 parts of sodium dodecylbenzenesulfonate are added to 300 parts of deionized water, stirred to dissolve, and slowly dripped into the epoxy core liquid, and emulsified at high speed of 1200 r / min for 30 min to form an oil-in-water emulsion with droplet size of 1-3 μm; 2) Mix 30 parts of tannic acid-modified urea with 60 parts of 37% formaldehyde aqueous solution, adjust the pH to 8 and stir for 60 min to generate urea-formaldehyde prepolymer; 3) The urea-formaldehyde prepolymer was slowly added dropwise to the emulsion system, and the pH was adjusted to 2-3 with dilute hydrochloric acid. The mixture was stirred at 60°C for 2.5 hours. The prepolymer gradually condensed on the surface of the oil droplets to form urea-formaldehyde resin capsule walls. Dilute ammonia was added dropwise to adjust the pH to neutral, and the mixture was allowed to settle. The mixture was then filtered, washed three times with water, and dried under vacuum at 40°C to obtain dry urea-formaldehyde shell epoxy microcapsule powder with a particle size of 1-3 μm.

[0035] Preparation Example 3 Preparation of acylhydrazone prepolymer: 1 mol adipamide and 1 mol terephthalaldehyde were dissolved in 800 mL of anhydrous ethanol, and 0.1 mol glacial acetic acid was added to adjust the pH of the system to 4. The mixture was stirred at room temperature for 3 h to generate a solid precipitate. After filtration, the filter cake was washed three times with anhydrous ethanol and dried under vacuum at 45 °C for 6 h to obtain the prepolymer.

[0036] Preparation Example 4 Preparation of tannin-based polyhydroxy modifier: 100 parts by weight of tannic acid were dissolved in 450 parts of anhydrous ethanol, and then 35 parts of trimethylolpropane triglycidyl ether were added. After stirring evenly, triethylamine was added to control the pH=8. The temperature was raised to 65℃ and stirred for 4 hours. After the reaction was completed, all the ethanol solvent was removed by vacuum distillation. After cooling and solidification, the product was obtained.

[0037] Example 1

[0038] A composite fiber material for safety ropes with high tensile strength and self-healing function has a three-layer coaxial gradient composite fiber structure, consisting of a load-bearing core layer, an intermediate functional layer, and a protective skin layer from the inside out; the load-bearing core layer accounts for 68% of the radial thickness, the intermediate functional layer for 24%, and the protective skin layer for 8%. The load-bearing core layer is composed of UHMWPE filament and para-aramid filament in a mass ratio of 75:25; The intermediate functional layer, by weight, comprises the following raw materials: 100 parts polyether-type 90A polyurethane, 2.5 parts 4,4'-diaminodiphenyl sulfide, 2.0 parts acylhydrazone prepolymer, 1.5 parts tannin-based polyhydroxy modifier, 1.2 parts aramid nanofibers, 1.0 part conductive filler (graphene to chopped multi-walled carbon nanotubes in a mass ratio of 1:3), 0.3 parts carbodiimide, and 5 parts urea-formaldehyde shell epoxy microcapsules. The protective skin, by weight, comprises: 100 parts weather-resistant polyurethane, 6.0 parts nano alumina, 2.0 parts UV absorber UV-531, and 4.0 parts tannin-based polyhydroxy modifier.

[0039] The urea-formaldehyde shell epoxy microcapsules were obtained from Preparation Example 2; the acylhydrazone prepolymer was obtained from Preparation Example 3; and the tannin-based polyhydroxy modifier was obtained from Preparation Example 4. The preparation process of the composite fiber material in this embodiment includes the following steps: S1. The UHMWPE and para-aramid blended filaments were subjected to air plasma treatment, then immersed in Tris-HCl buffer containing dopamine hydrochloride for in-situ grafting, and washed and dried. Specific parameters: plasma power 300W, treatment time 100s; buffer pH=8.5, dopamine hydrochloride concentration 2.0g / L, reaction time at room temperature 2.5h; S2. Preparation of intermediate functional layer masterbatch: First, vacuum dry polyether type 90A polyurethane at 80℃ for 4 hours. Add all organic functional additives to a high-speed mixer and stir at room temperature for 15 minutes. Then transfer to an ultrasonic reactor and ultrasonically disperse at 20kHz for 30 minutes. Cool down to system temperature <60℃ and stirring speed ≤150r / min and mix in urea-formaldehyde shell epoxy microcapsules. Feed the mixture into a twin-screw extruder, control the processing temperature at 175℃ (residence time in each zone of the screw ≤60s), extrude and water-cool pelletize to obtain intermediate functional layer masterbatch. Preparation of protective skin masterbatch: Weather-resistant polyurethane particles were vacuum dried at 80℃ for 4 hours, and then all materials were put into a high-speed mixer and stirred at room temperature for 10 minutes; then transferred to an ultrasonic reactor and ultrasonically dispersed at 20kHz for 15 minutes; finally fed into a twin-screw extruder, extruded at 170℃, and water-cooled and pelletized to obtain protective skin masterbatch. S3. The modified blended filaments obtained in S1, the intermediate functional layer masterbatch obtained in S2, and the protective skin layer masterbatch are fed into a three-layer coaxial gradient melt spinning equipment. The core layer barrel is melt-co-extruded at 190°C, the intermediate functional layer barrel at 180°C, and the protective skin layer barrel at 170°C. The spinning speed is 800 m / min, and the spinning is air-cooled at 25°C. The nascent filaments are sequentially subjected to a first-stage hot stretching at 95°C with a stretch ratio of 1.8 and a second-stage hot stretching at 110°C with a stretch ratio of 1.4. Then, they are sent to -15°C for deep cryogenic tempering for 20 min to obtain the nascent composite fiber material.

[0040] Example 2

[0041] A composite fiber material for safety ropes with high tensile strength and self-healing function and its preparation process are described. The specific implementation method is the same as in Example 1, except that: The intermediate functional layer, by weight, comprises the following raw materials: 100 parts polyether-type 90A polyurethane, 2.0 parts 4,4'-diaminodiphenyl sulfide, 1.5 parts acylhydrazone prepolymer, 1.0 part tannin-based polyhydroxy modifier, 1.0 part aramid nanofibers, 0.8 parts conductive filler (graphene to chopped multi-walled carbon nanotubes in a mass ratio of 1:2), 0.2 parts carbodiimide, and 4.0 parts urea-formaldehyde shell epoxy microcapsules; The protective coating, by weight, comprises: 100 parts weather-resistant polyurethane, 4.0 parts nano alumina, 1.5 parts UV absorber UV-531, and 3.0 parts tannin-based polyhydroxy modifier.

[0042] Example 3

[0043] A composite fiber material for safety ropes with high tensile strength and self-healing function and its preparation process are described. The specific implementation method is the same as in Example 1, except that: The intermediate functional layer, by weight, comprises the following raw materials: 100 parts polyether-type 90A polyurethane, 3.0 parts 4,4'-diaminodiphenyl sulfide, 2.5 parts acylhydrazone prepolymer, 2.0 parts tannin-based polyhydroxy modifier, 1.5 parts aramid nanofibers, 1.2 parts conductive filler (graphene to chopped multi-walled carbon nanotubes in a mass ratio of 1:4), 0.4 parts carbodiimide, and 6.0 parts urea-formaldehyde shell epoxy microcapsules; The protective coating, by weight, comprises: 100 parts weather-resistant polyurethane, 8.0 parts nano alumina, 2.5 parts UV absorber UV-531, and 5.0 parts tannin-based polyhydroxy modifier.

[0044] Example 4

[0045] A composite fiber material for safety ropes with high tensile strength and self-healing function and its preparation process are described. The specific implementation method is the same as in Example 1, except that: no urea-formaldehyde shell epoxy microcapsules are added to the middle functional layer.

[0046] Example 5

[0047] A composite fiber material for safety ropes with high tensile strength and self-healing function and its preparation process are disclosed. The specific implementation method is the same as in Example 1, except that no conductive filler is added to the middle functional layer.

[0048] Comparative Example 1 A composite fiber material and its preparation process are described. The specific implementation method is the same as in Example 1, except that: no aromatic disulfide chain extender and acylhydrazone prepolymer are added to the intermediate functional layer.

[0049] Comparative Example 2 A composite fiber material and its preparation process are described. The specific implementation method is the same as in Example 1, except that the fiber filaments supporting the core layer are only subjected to 300W, 100s plasma treatment, and dopamine hydrochloride grafting treatment is not performed.

[0050] Comparative Example 3 A composite fiber material and its preparation process are described. The specific implementation method is the same as in Example 1, except that the protective skin layer does not contain tannin-based polyhydroxy modifiers.

[0051] Comparative Example 4 The traditional preparation steps for externally coated self-healing aramid / UHMWPE composite fibers are as follows: S1. Treat the UHMWPE / para-aramid blended filament with air plasma at 300W for 100s. After treatment, rinse with ethanol and dry directly. S2. By weight, dissolve 12 parts of polyether-type 90A polyurethane in 100 parts of anhydrous ethanol at room temperature, stir until completely dissolved, add 8 parts of tannin-based polyhydroxy modifier, stir evenly, and obtain a transparent repair coating liquid.

[0052] S3. The plasma-treated fiber is continuously impregnated with the coating liquid at an impregnation speed of 5m / min. After removal, it is dried with hot air at 100℃ to form a single-layer self-healing coating with a thickness of about 10μm on the fiber surface. S4. The coated fiber is subjected to a first-stage hot stretching at 95℃ with a ratio of 1.8, a second-stage hot stretching at 110℃ with a ratio of 1.4, and then deep-cold tempering at -15℃ for 20 minutes to obtain the final product.

[0053] Performance testing: The following performance tests were conducted on the composite fiber materials of each embodiment and comparative example.

[0054] Test conditions: Temperature 25℃, relative humidity 70%.

[0055] Test methods Composite fiber tensile strength: Refer to GB / T1040 standard; 2) Self-healing efficiency: The specimen was pre-cracked with a 0.05mm fine crack and a 0.15mm deep crack. After the external force was completely broken, the fracture surfaces were bonded together and left to stand at 25℃ and 70% RH for 30 minutes. The tensile strength was then retested. Self-healing efficiency = fracture strength after repair ÷ initial fracture strength × 100%; 3) Strength retention rate after 5 cycles of repair: The same location is repeatedly stretched to produce cracks and repaired. The strength retention rate is measured after 5 cycles. 4) Damage warning resistance change: A digital high-precision resistance tester is used to record the resistance difference before and after the crack occurs; 5) Aging resistance: Referring to GB / T16422.2 standard, the initial strength and self-healing efficiency were retested after 500 hours using a xenon lamp weathering aging test chamber.

[0056] The test results are shown in Table 1.

[0057] Table 1

[0058] According to the data in Table 1, the composite fiber materials in Examples 1-3 can all achieve high tensile strength, self-healing in dry and wet environments, damage resistance early warning, and deep crack filling and repair.

[0059] As demonstrated in Examples 1 and 4, urea-formaldehyde shell epoxy microcapsules are used to fill and repair large-sized deep tear cracks. Except for the presence or absence of microcapsules, both examples are identical under the following conditions: at room temperature (25°C) and RH 70%, the self-repair efficiency for 0.05mm microcracks is similar (93.8% in Example 1 and 93.5% in Example 4). Microcracks can be healed through interface closure using only triple dynamic reversible bonds, without the need for microcapsules. However, for 0.15mm deep cracks, Example 1 with microcapsules achieves a repair efficiency of 92.1%, while Example 4 without microcapsules only achieves 67.8%, showing a significant performance difference. This is because large cracks cannot fully restore mechanical properties through intermolecular dynamic bond forces alone. When microcapsules rupture under stress, they release the epoxy core liquid, which cross-links and cures at room temperature, physically filling the crack and bridging the fracture surface, significantly improving the deep damage repair capability. Simultaneously, the microcapsules do not affect the material's tensile strength, cyclic repair stability, weather resistance, or electrical conductivity warning performance.

[0060] As shown in Examples 1 and 5, the graphene / carbon nanotube composite conductive filler is used to construct conductive pathways, enabling online early warning of internal hidden damage through the sudden change in resistance before and after crack formation. The two groups of samples showed essentially no difference in mechanical, self-healing, and weather resistance properties. In Example 1, containing the conductive filler, the resistance increase reached 220% after the formation of microcracks, allowing for direct identification of fatigue cracks invisible to the naked eye. In Example 5, without the conductive filler, the resistance showed no significant change after crack formation, completely losing its damage warning function. Low-dosage conductive filler can form a continuous three-dimensional conductive network within the matrix. Cracks interrupt the conductive pathways, causing a sharp increase in resistance. Furthermore, the low filler dosage does not damage the triple dynamic bond cross-linking system or the fundamental mechanical properties of the material.

[0061] Comparative Examples 1-3 lacked the triple dynamic bond synergistic system, fiber interface modification, and cortical self-healing protection, respectively. Compared with all embodiments of the present invention, the self-healing efficiency, mechanical strength, cycle stability, and weather resistance were significantly degraded. The specific analysis is as follows: Comparative Example 1 (only tannin with a single hydrogen bond, no disulfide bond or acylhydrazone bond) Relying on single tannin hydrogen bond repair lacks a complementary repair mechanism under various conditions, including dry, wet, and hot environments. At room temperature, the repair rate for fine cracks was 78.0%, and for deep cracks, it was 65.2%. After 5 cycles, the strength retention rate was only 65.8%. After xenon lamp aging, the repair efficiency was only 59.3%, far lower than in Example 1, demonstrating that the synergistic effect of triple dynamic bonds is the core of long-term self-repair in multiple environments.

[0062] Comparative Example 2, without dopamine fiber interface modification, showed poor adhesion between the fiber and TPU matrix, with an initial tensile strength of only 3.02 GPa, a significant decrease compared to Example 1. The cyclic repair retention rate, spinning stability, and weather resistance all deteriorated simultaneously, with a repair efficiency of only 76.1% after aging. This indicates that dopamine modification is a necessary condition for improving interfacial bonding and overall mechanical properties.

[0063] Comparative Example 3, which does not contain tannin modifier, has short-term mechanical and self-healing properties similar to Example 1, but surface scratches cannot be self-repaired. After 500 hours of xenon lamp aging, the internal dynamic bonds degrade rapidly, and the repair efficiency after aging is only 71.8%, which is much lower than that of Example 1. This confirms that the tannin modifier in the cortex can self-heal the surface and delay the aging of the internal functional layer.

[0064] Comparative Example 4 is a mainstream existing technology solution with externally coated self-healing fibers. Its mechanical strength, self-healing ability, weather resistance, and damage warning are all inferior to the three-layer coaxial integrated embedded functional layer structure of this invention.

[0065] To further verify the self-healing stability of the composite fiber of the present invention in complex outdoor environments, self-healing tests were conducted on the composite fibers of Examples 1-3 and Comparative Example 1 under three typical working conditions: low temperature in winter (5℃, RH60%), high humidity in rainy weather (25℃, RH95%), and dry heat and sun exposure in summer (50℃, RH20%). The test results are shown in Table 2.

[0066] Table 2

[0067] As shown in Table 2, under the full conditions of 5℃ low temperature, 95% high humidity, and 50℃ dry heat, Examples 1-3 all showed a microcrack repair efficiency of over 81% and a deep crack repair efficiency of over 78%. The triple dynamic reversible bond formation complementary and synergistic mechanism is as follows: the rapid dynamic exchange of aromatic disulfide bonds at high temperature enhances the repair capacity; the acylhydrazone bonds in the high humidity environment play a moisture-responsive repair role; and the tannin hydroxyl hydrogen bonds serve as the basic room-temperature repair network, achieving long-term self-healing in multiple environments.

[0068] In contrast, Comparative Example 1 uses only a single tannin hydrogen bond system. Under high humidity conditions, the hydrogen bonds are dissociated by water molecules, resulting in a deep crack repair efficiency of less than 40%. Under low temperature conditions, the sluggish molecular chain movement further diminishes the self-healing ability, and only in dry, high-temperature environments does it have a limited repair effect. This demonstrates that the aromatic disulfide bond, acylhydrazone bond, and tannin hydrogen bond complex system of this invention, compared to existing single tannin self-healing schemes, has the effect of adapting to multiple working conditions.

[0069] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A composite fiber material for safety ropes with high tensile strength and self-healing function, characterized in that, The composite fiber material has a three-layer coaxial gradient composite fiber structure, consisting of a load-bearing core layer, an intermediate functional layer, and a protective skin layer from the inside out; based on the radial thickness percentage, the load-bearing core layer accounts for 65%–70%, the intermediate functional layer for 20%–25%, and the protective skin layer for 5%–10%. The load-bearing core layer is composed of UHMWPE filament and para-aramid filament; The intermediate functional layer, by weight, comprises the following raw materials: 100 parts polyether-type polyurethane elastomer, 2.0-3.0 parts aromatic disulfide chain extender, 1.5-2.5 parts acylhydrazone prepolymer, 1.0-2.0 parts tannin-based polyhydroxy modifier, 1.0-1.5 parts aramid nanofibers, 0.8-1.2 parts conductive filler, and 0.2-0.4 parts hydrolysis stabilizer; The protective skin layer comprises, by weight, the following raw materials: 100 parts weather-resistant polyurethane, 4.0 to 8.0 parts nano alumina, 1.5 to 2.5 parts ultraviolet absorber, and 3.0 to 5.0 parts tannin-based polyhydroxy modifier.

2. The composite fiber material for safety ropes according to claim 1, characterized in that, The conductive filler is a composite of graphene and short-cut multi-walled carbon nanotubes, with a mass ratio of 1:(2-4).

3. The composite fiber material for safety ropes according to claim 1, characterized in that, The raw materials for the intermediate functional layer also include 4.0 to 6.0 parts by weight of urea-formaldehyde shell epoxy microcapsules, wherein the particle size of the urea-formaldehyde shell epoxy microcapsules is 1 to 3 μm.

4. The composite fiber material for safety ropes according to claim 1, characterized in that, The mass ratio of UHMWPE filament to para-aramid filament in the bearing core layer is 70-80:20-30; the fineness of both fibers is 1.2-1.5D, and the tensile strength of each fiber is ≥3.8GPa.

5. The composite fiber material for safety ropes according to claim 1, characterized in that, The surface of the core fiber is modified by in-situ grafting of dopamine hydrochloride after plasma activation, and a polydopamine nano-adhesive layer is formed on the fiber surface.

6. The composite fiber material for safety ropes according to claim 1, characterized in that, The tannin-based polyhydroxy modifier is obtained by reacting tannic acid and trimethylolpropane triglycidyl ether at a mass ratio of 1:(0.3-0.4) under weak alkali catalysis at 60-70℃ with stirring and then removing solvent.

7. The composite fiber material for safety ropes according to claim 1, characterized in that, The composite fiber material has a tensile strength ≥3.3GPa; its self-repair efficiency for 0.05mm fine cracks is ≥88% after 30 minutes at 25℃ and RH70% conditions, and its strength retention rate is ≥86% after repeated repairs at the same location 5 times.

8. A process for preparing the composite fiber material for safety ropes according to any one of claims 1 to 7, characterized in that, It includes the following steps: S1. The UHMWPE and para-aramid blended filaments were subjected to air plasma treatment, then immersed in Tris-HCl buffer containing dopamine hydrochloride for in-situ grafting, and washed and dried. S2. Prepare intermediate functional layer masterbatch and protective skin layer masterbatch according to the formula ratio respectively; S3, three-layer coaxial gradient melt spinning, followed by two-stage hot stretching and deep cryogenic tempering to obtain nascent composite fiber material.

9. The preparation process of the composite fiber material for safety ropes according to claim 8, characterized in that, Step S1 modification conditions: plasma power 200-400W, treatment for 90-120s; buffer pH=8-9, dopamine hydrochloride concentration 1.8-2.2g / L, reaction at room temperature for 2-3h, and drying.

10. The preparation process of the composite fiber material for safety ropes according to claim 8, characterized in that, In step S2, when preparing the intermediate functional layer masterbatch, the nanofiller is ultrasonically dispersed at 15-25kHz. When it contains urea-formaldehyde shell epoxy microcapsules, the mixing should be controlled under the conditions of system temperature <60℃ and stirring speed ≤150r / min. The twin-screw granulation temperature is 165~180℃.